Pemanfaatan Media Sosial Instagram dalam Membangun Brand Awareness Wedding Organizer Rumah Pengantin Yuniskha - Fachri Affandi; Alisha Aulia Pinggadini; Erwin Permana; Ateniyanti Ateniyanti (LPPM Politeknik Pratama, 2026)
This study aims to analyze the use of Instagram as a promotional medium for Rumah Pengantin Yuniskha and its impact on brand awareness and business growth. A descriptive qualitative method was employed, using data from internal company records and related scientific publications. The results indicate that a more structured Instagram management strategy, with varied content such as event documentation, short tips, reels, and stories, increased account visits, audience interaction, and prospective clients, positively affecting service package sales. These findings suggest that consistent and strategic use of social media can strengthen brand awareness and serve as an effective marketing management tool to support the growth of wedding organizer businesses.